(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
Gamification has proven effective in grammar instruction across diverse linguistic contexts, revealing notable similarities in its application to foreign language (English) and mother tongue (Uzbek) teaching. This literature review highlights shared benefits, including enhanced motivation, engagement, reduced anxiety, and improved retention through interactive and contextual activities. Anthropocentric paradigms underscore these parallels by framing grammar as a human-centered cognitive process, where games embed structures in experiential and relational contexts regardless of language status. Evidence from Uzbek primary and higher education, combined with broader EFL studies, demonstrates universal pedagogical advantages. Implications recommend unified gamified frameworks to foster communicative competence in multilingual settings.